Występowanie czeremchy amerykańskiej (Prunus serotina Ehrh.) w Lasach Państwowych - Bijak, Szymon; Czajkowski, Maciej; Ludwisiak, Łukasz (Leśne Prace Badawcze, 2014)
Among the invasive tree species identified in Polish forests, black cherry ( Prunus serotina Ehrh.) appears to pose the greatest threat. The objective of this study was i), to determine the abundance of this species in the forests managed by the State Forests National Forest Holding (PGLLP) and ii), to characterise the ecological conditions that it is found in. The source data was obtained from the State Forests Information System (SILP) database. In Polish forests, black cherry mostly occurs as an understory plant and is present in a total area of 99,185 hectares, which is 1.4% of the forest area under the management of the PGLLP. Although Prunus serotina can be found within a wide range of habitats, it most commonly occurs on sites that can be considered average in terms of fertility (mixed coniferous and mixed deciduous types) developed primarily on rusty soils (podzols).